Identity elements for the aminoacylation of metazoan mitochondrial tRNA(Arg) have been widely conserved throughout evolution and ensure the fidelity of the AGR codon reassignment - Igloi, Gabor L (RNA Biol, 2015)
Eumetazoan mitochondrial tRNAs possess structures (identity elements) that require the specific recognition by their cognate nuclear-encoded aminoacyl-tRNA synthetases. The AGA (arginine) codon of the standard genetic code has been reassigned to serine/glycine/termination in eumetazoan organelles and is translated in some organisms by a mitochondrially encoded tRNA(Ser)(UCU). One mechanism to prevent mistranslation of the AGA codon as arginine would require a set of tRNA identity elements distinct from those possessed by the cytoplasmic tRNAArg in which the major identity elements permit the arginylation of all 5 encoded isoacceptors. We have performed comparative in vitro aminoacylation using an insect mitochondrial arginyl-tRNA synthetase and tRNAArgUCG structural variants. The established identity elements are sufficient to maintain the fidelity of tRNASerUCU reassignment. tRNAs having a UCU anticodon cannot be arginylated but can be converted to arginine acceptance by identity element transplantation. We have examined the evolutionary distribution and functionality of these tRNA elements within metazoan taxa. We conclude that the identity elements that have evolved for the recognition of mitochondrial tRNAArgUCG by the nuclear encoded mitochondrial arginyl-tRNA synthetases of eumetazoans have been extensively, but not universally conserved, throughout this clade. They ensure that the AGR codon reassignment in eumetazoan mitochondria is not compromised by misaminoacylation. In contrast, in other metazoans, such as Porifera, whose mitochondrial translation is dictated by the universal genetic code, recognition of the 2 encoded tRNAArgUCG/UCU isoacceptors is achieved through structural features that resemble those employed by the yeast cytoplasmic system.